Real Time Monitoring for the Most Vulnerable: Pre‐Primary Education in Bangladesh. (21st March 2013) - Akhter, Mahmuda; Chaudhuri, Jay
Abstract One of the most unique examples of real‐time monitoring supported by UNICEF is found in Bangladesh in the pre‐primary education (PPE) programme operated by BRAC. Randomisation techniques are used for school selection by monitors as well as for intra‐classroom sampling to test learning outcomes. Monitoring is a multi‐level decentralised learning process that allows staff members to compare actual performance, outputs and results against standards. Monitoring duties are executed by the programme staff themselves as well as by the organisation. The intent is to promote internal programme learning, not just logical framework type reporting, and builds on the recognition that monitoring is only effective if it enables responses to programme implementation. The BRAC initiative demonstrates that monitoring with a real‐time component can be central to a strategy emphasising learning outcomes. It also shows that ICTs are not a necessary ingredient of 'real‐time' monitoring despite the current fashion in thinking.